2014
DOI: 10.9790/1959-03255863
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy Of 0.2% Chlorhexidine versus Herbal Oral Rinse on Plaque Induced Gingivitis- A Randomized Clinical Trail

Abstract: Background: Supragingival plaque control is fundamental to the prevention and management of periodontal diseases. However significant proportions of all individuals fail to practice a high standard of plaque removal. The adjunctive use of chemicals would, therefore appear a way of overcoming deficiencies in mechanical tooth cleaning habits. This prospective, randomized positively controlled clinical trial was designed to evaluate the short-term clinical effects of a Herbal mouthwash in the reduction of plaque … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
1
14
0
1
Order By: Relevance
“…Herbal mouthwash becomes more popular they work without alcohol, artificial preservatives, flavor, or colors [5]. As it contains natural herbs that have natural cleansing and healing property to teeth and gums.…”
Section: Herbal Mouthwashmentioning
confidence: 99%
See 2 more Smart Citations
“…Herbal mouthwash becomes more popular they work without alcohol, artificial preservatives, flavor, or colors [5]. As it contains natural herbs that have natural cleansing and healing property to teeth and gums.…”
Section: Herbal Mouthwashmentioning
confidence: 99%
“…Some of the herbs that are used in mouthwashes are clove, which is traditionally used for oral health because of their antiseptic, antibacterial, and antiviral property, peppermint which gives cooling effect to the mouth, plantain has ability for speed wound healing and many of the herbs contains anti-microbial, anti-inflammatory, antioxidants, antiseptic properties such as neem, clove, triphala with combination of amalaki, haritaki, vibhitaki, tulsi, celery, licorice, oak tree, bakula, katha, spearmint, turmeric, and Aloe vera. [5].…”
Section: Herbal Mouthwashmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of tannin which is present to an extent of 30-40 % may have induced cytotoxic action on the cell membranes of the microorganism. A study done by Gautam Biswas et al 21 showed a significant reduction in Plaque scores from baseline to 1 st week, 2 nd week and at 4 th week in both chlorhexidine and herbal mouthwash. But the improvement in plaque index scores were found better in Chlorhexidine group compare to herbal mouthwash group.…”
Section: Discussionmentioning
confidence: 96%
“…There are a number of polyherbal toothpastes playing an important role in dental prophylaxis and improvement of oral health [ 31 ]. In a study conducted by Sekar and Zulhilmi Abdullah, S. aureus was reported as the most sensitive species to polyherbal toothpaste with an inhibition zone of 10-15 mm, followed by E. coli (9-12 mm), Bacillus cereus (7-12 mm), and Pseudomonas aeruginosa (9-11 mm) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%